1971
DOI: 10.1001/archpedi.1971.02100150052002
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Enzymic Cleavage of β-Carotene

Abstract: A 10-year-old Lebanese Arab girl had vitamin A deficiency as evidenced by night blindness, bilateral Bitot's spots, and very low plasma vitamin A concentration (7\g=m\g/ 100 ml). Total plasma carotenoid values were high with about 50% as \g=b\-carotene. Repeated blood sampling after large doses of \g=b\-carotene failed to produce any retinyl ester in the plasma whereas there was significant rise of ester levels in three control subjects. Preformed vitamin A cured the clinical condition and caused retinyl ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…To date, only a few studies have described the same phenomenon that we observed in the Agogo 2000 birth cohort study [46,47]. Genetic variants have previously contributed to the interindividual variability of plasma carotenoids, mainly in non-African populations [20].…”
Section: Bco1 Variants and Carotenoid Concentrationsmentioning
confidence: 53%
“…To date, only a few studies have described the same phenomenon that we observed in the Agogo 2000 birth cohort study [46,47]. Genetic variants have previously contributed to the interindividual variability of plasma carotenoids, mainly in non-African populations [20].…”
Section: Bco1 Variants and Carotenoid Concentrationsmentioning
confidence: 53%
“…Low protein diets reduced dioxygenase activity in rats (Gronowska-Senger & Wolf, 1970). Failure to split 8-carotene in man is rare but can lead to metabolic carotenaemia at low intakes of carotenoids (Monk, 1982) or to vitamin A deficiency if retinol intake is low (McLaren & Zekian, 1971).…”
Section: O N V E R S I O N O F C a R O T E N O I D S T O R E T I N O Lmentioning
confidence: 99%